How to leverage outward FDI for development? A six-step guide for policymakers - Matthew Stephenson; Jose Ramon Perea (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
OFDI can increasingly serve as an additional channel for countries to achieve their development goals. This Perspective proposes a six-step framework to help policymakers think through how best to facilitate, support and promote OFDI to maximize the benefits for the home economy.
Keywords: 330